ANALISIS PERAN PROGRAM STUDI PENDIDKAN GURU SEKOLAH DASAR (PGSD) DALAM MENINGKATKAN KOMPETENSI CALON GURU SEKOLAH DASAR - Elysa Randa Lino (Lembaga Pengembangan Inovasi Pendidikan Baiturrahman, 2026)
The Elementary School Teacher Education Program (PGSD) plays a strategic role in preparing prospective teachers who are competent and professional at the primary education level. This article aims to analyze in depth the role of PGSD in improving the competencies of prospective elementary school teachers using a literature study method. Data sources were obtained from various scientific journals, academic books, and relevant previous research. The results of the study indicate that PGSD plays an important role in developing pedagogical, professional, social, and personal competencies through the implementation of competency-based curricula, practice-based learning, strengthening digital literacy, and character development. In addition, collaboration between universities and partner schools is also an important factor in enhancing the readiness of prospective teachers. With systematic and adaptive management in response to current developments, PGSD is capable of producing graduates who are ready to face the challenges of 21st-century education.